NEW BINARY SYSTEMS WITH ASYMMETRIC LIGHT CURVES - Virnina, N. A. (Одеські астрономічні публікації, 2010)
We present the results of investigation of the light curves of 27 newly discovered binary systems. Among the examined curves, there were 10 curves with statistically significant asymmetry of maximums, according the 3σ criterion for the difference between the maximal brightness. Half of these 10 curves have a higher first maximum, another half the second one. Two of these 10 curves, USNO-B1.0 1629-0064825 = VSX J052807.9+725606 and USNO-B1.0 1586-0116785, show the largest difference between magnitudes in maxima. The star VSX J052807.9+725606 also shows the secondary minimum, which is shifted from the phase φ = 0.5. The shape of the curve argues that the physical processes of this star could be close to that of well known short periodic binary system V361 Lyr, which has a spot on the surface of one star of the system. Another star, USNO-B1.0 1586-0116785, probably has a cold spot, or several spots, in the photosphere of one of the components.